"I’m Not Gay - Not That There’s Anything Wrong with That!": Are Unwanted Imputations of Gayness Defamatory? - Knight, Dean R (Victoria University of Wellington Law Review, 2006)
The question of whether unwanted imputations of gayness are defamatory continues to be controversial. This article considers whether a person can bring a defamation claim if they have been described as being gay or lesbian. In particular, this article addresses whether such an imputation is defamatory, including whether such an imputation tends to lower the reputation of a person in the estimation of “right-thinking” members of society, and the unique issues that this imputation presents for possible defences. In addition to assessing the present position, this article considers whether imputations of gayness ought to be defamatory, particularly in the context of today’s legal environment. It is argued that an imputation of gayness should not be treated as being defamatory in the light of the reforms of gay and lesbian rights, including the anti-discrimination and equality protections that are now commonplace in Anglo-Commonwealth societies.